2018
DOI: 10.1007/s11121-018-0892-7
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Gay Couples’ Motivations to Use (or Forego) Pre-exposure Prophylaxis Expressed During Couples HIV Testing and Counseling (CHTC) Sessions

Abstract: While many gay couples perceive themselves to have little risk for HIV transmission, research estimates that 35-68% of new HIV infections are transmitted within main partnerships. Pre-exposure prophylaxis (PrEP) is recommended for those partnered gay and bisexual men (GBM) who engage in sex outside their primary relationship or who have an HIV-positive partner. There is reason to believe that couples' sero-status and sexual agreement will shape perceptions of PrEP's personal relevance among gay couples. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Although it has been suggested that PrEP uptake is likely to increase over time as awareness and knowledge improve among patients (Strauss et al, 2017) and providers (Petroll et al, 2017), it is likely that bisexual men will continue to be less likely to use PrEP than gay men unless it is specifically marketed to bisexual men and providers are educated about the disparities affecting this population. Relatedly, prior studies assessing PrEP (knowledge of, attitudes toward, and willingness to use) have focused on samples of "gay and bisexual men" or "MSM" (Carballo-Dieguez et al, 2017;Mimiaga et al, 2018;Parsons, John, Whitfield, Cienfuegos-Szalay, & Grov, 2018;Starks, Doyle, Shalhav, John, & Parsons, 2018), and, to date, no studies have examined unique barriers to PrEP use among bisexual men. Research on PrEP has also not been intentionally inclusive of bisexual men, nor has it focused on their potentially unique PrEP-related concerns and needs.…”
Section: The Movement Toward Biomedical Hiv Preventionmentioning
confidence: 99%
“…Although it has been suggested that PrEP uptake is likely to increase over time as awareness and knowledge improve among patients (Strauss et al, 2017) and providers (Petroll et al, 2017), it is likely that bisexual men will continue to be less likely to use PrEP than gay men unless it is specifically marketed to bisexual men and providers are educated about the disparities affecting this population. Relatedly, prior studies assessing PrEP (knowledge of, attitudes toward, and willingness to use) have focused on samples of "gay and bisexual men" or "MSM" (Carballo-Dieguez et al, 2017;Mimiaga et al, 2018;Parsons, John, Whitfield, Cienfuegos-Szalay, & Grov, 2018;Starks, Doyle, Shalhav, John, & Parsons, 2018), and, to date, no studies have examined unique barriers to PrEP use among bisexual men. Research on PrEP has also not been intentionally inclusive of bisexual men, nor has it focused on their potentially unique PrEP-related concerns and needs.…”
Section: The Movement Toward Biomedical Hiv Preventionmentioning
confidence: 99%
“…This subsequently promotes adaptive or constructive responses such as problem-solving or providing emotional support (sometimes referred to as accommodation) in response to disagreements or inconsiderate behavior (Rusbult & Van Lange, 2003 ; Rusbult et al, 1983 , 1991 ). Consistent with the overall premise of Interdependence Theory, research with SMM, specifically, has illustrated associations between dimensions of relationship functioning and a range of health outcomes, including condom use (Davidovich et al, 2006 ; Goldenberg et al, 2015 ; Mitchell & Petroll, 2013 ; Starks et al, 2014 ), HIV medication adherence (Goldenberg et al, 2013 ; Johnson et al, 2012 ), pre- and post-exposure prophylaxis to prevent HIV (Bosco et al, 2021 ; Gamarel & Golub, 2019 ; Starks et al, 2019b ), and substance use (Starks et al, 2019d ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, SMM who believed themselves to be at a higher risk of HIV acquisition were more likely to engage in regular testing (Stephenson et al, 2015a ). Although investigations in this area are limited, there is some evidence to suggest that SMM couples who perceive HIV transmission as a significant health threat and perceive the management of HIV transmission risk as a shared responsibility are more likely to engage in risk reduction strategies (e.g., condom use, PrEP uptake; Gamarel et al, 2014 ; Starks et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Further underscoring this importance, the CDC PrEP guidelines make specific recommendation to prescribe PrEP to MSM and all people in serodifferent relationships [2]. Previous research has also shown that serodifferent relationship status may be a primary driver for patients to seek PrEP to mitigate the risk of HIV transmission to the HIV-negative partner [28]. Patients in serodifferent relationships have expressed interest in PrEP as a method for protection from HIV and to decrease anxiety about HIV transmission during sex [29].…”
Section: Introductionmentioning
confidence: 99%